Domestic Factors That Affect The Price of Styrene Butadiene Latex in Indonesia - Nugroho, Rosalendro Eddy (Muhammadiyah University Press, 2019)
This paper investigates or examines the causal links between price of styrene butadiene latex (SBL) and other domestic variables such as supply, demand, Herfindahl Hirschman Index (HHI), price of styrene, and price of butadiene during the period of 1995–2017 on the monthly basis.. Results from Augmented Dickey Fuller (ADF) or unit root test showed that the stationary state of the whole variables is of first difference (I). The Granger pairwise causality test revealed a bidirectional causality of SBL with BTD(Butadiene), SBL with STY(Styrene), SUPP(Supply) with DMD(Demand), DMD with STY, DMD with BTD and STY with SUPP and vice versa. Johansen test found out a co-integration of SBL prices. However, this study proved no significant links between the price of SBL and supply of SBL (SUPP) in the long and short run. This paper highlights the fact that SBL price has a significant direct impact in the long run on the styrene (STY) and butadiene (BTD) prices, as well as HHI. Similarly, these aspects also have a significant direct impact proved by the positive coefficient in the long run on the SBL pricing. The findings further showed that the price of SBL has a connection and significant direct impact on the negative arrow for the short and long run equilibrium, in line with the price and demands for SB Latex, pressing and oil classification.